PELAKSANAAN SEPERVISI PENGAWAS PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MUTU PEMBELAJARAN PAI - Ujang Sofyan (UNISAN JURNAL, 2024)
This examination plans to break down the execution of administrative oversight in working on the nature of Islamic learning at SD Negeri 20 Talang Ubi, as well as the deterrents and systems that can be carried out to upgrade its execution. The examination strategy utilized is subjective with information assortment procedures through meetings, perception and documentation. The consequences of the examination show that the execution of administrative management at SD Negeri 20 Talang Ubi has been completed regularly and organized utilizing a few different oversight strategies and methods to work on the nature of Islamic learning in schools. In any case, a few obstructions were as yet experienced in its execution, like restricted HR, absence of arranging and using time productively, as well as absence of help and support from educators and managerial staff. Subsequently, bosses can enhance the execution of oversight by carrying out compelling methodologies, like expanding HR through preparing and creating instructor impressive skill, as well as further developing using time productively by making an arranged and organized management plan. To work on the nature of Islamic schooling at SD Negeri 20 Talang Ubi, persistent endeavors and responsibility are required from all connected gatherings to keep on making enhancements and advancements in the execution of oversight, human asset improvement, using time productively, and cooperative energy between all gatherings. party at school.